Sunday

April 20, 2014

April 20, 2014

Posted by **Chanell** on Sunday, April 10, 2011 at 4:21pm.

- geometry -
**Henry**, Tuesday, April 12, 2011 at 2:41pmEq1: X + Y = 11.

Eq2: Y + Z = 14.

Y = 14 - Z.

Eq3: X + Z = 13.

X = 13 - Z.

In Eq1, substitute (13-Z) for X, and

(14-Z) for Y:

(13-Z) + (14-Z) = 11,

13 - Z + 14 - Z = 11,

-2Z + 27 = 11,

-2Z = 11 - 27 = -16,

Z = 8.

X + Y + Z,

Substitute 11 for y and 8 for Z:

(X+Y)+Z = 11 + 8 = 19.

- geometry -
**Henry**, Tuesday, April 12, 2011 at 2:46pmCORRECTION:

Substitute 11 for (x+y).

**Related Questions**

statistics - What is your conclusion based on the following data? A survey was ...

Java - 1 public class testOperators 2 { 3 public static void main(String[] args...

Java - I need help putting the following trace into pseudocode 1 public class ...

statistics - For the following data independent samples, could the null ...

Statistics - The ages (in years) of 10 infants and the number of hours each ...

Matrh - How do you solve this problem? The avera&e (aritmeticmean)of x and y is ...

statistics - The ages (in years) of 10 infants and the number of hours each ...

Math-geometry - This is so confusing :( Given U = {10, 11, 12, 13, 14, 15, 16, ...

geometry - equation of a line with the co-ordinates(10,0),(11,2),(12,4),(13,6) ...

math help please - 12. (-8x) x (3x^2) -5x^3 -24x^2 -24x^3 -5x^2 13. (-11z)^0 z 1...